Pembelajaran Keterampilan Dasar THT untuk Siswa SMA Negeri 9 Pekanbaru Sebagai Upaya Promosi Kesehatan Sekolah - Arnila Melina; Donny Haryxon Tobing; Hidayatul Fitria; Retno Putri (Pusat Riset dan Inovasi Nasional, 2026)
Ear, Nose, and Throat (ENT) health is an essential component of adolescents’ well-being and learning performance; however, health literacy related to ENT care among senior high school students remains limited. This community service activity aimed to improve students’ knowledge and basic ENT skills at SMA Negeri 9 Pekanbaru through skill lab–based learning as a school health promotion strategy. The program was conducted through theoretical education covering basic ENT anatomy and common ENT disorders among adolescents, followed by hands-on training in simple ENT examinations using demonstration and direct practice with learning aids. Evaluation was carried out using pre-test and post-test assessments to measure knowledge improvement, as well as direct observation to assess students’ practical skills. The results demonstrated a clear increase in students’ knowledge after the intervention, along with improved ability to perform basic ENT examinations under instructor guidance. Students also showed better understanding of early signs of ENT disorders and appropriate preventive behaviors. Participation and enthusiasm during the activities were high, and most students reported that the program was beneficial and relevant to their daily experiences. This activity also supported the School Health Unit (UKS) program and strengthened collaboration between the school and the university. In conclusion, skill lab–based basic ENT training is an effective promotive and preventive approach to enhancing ENT health literacy and basic clinical skills among senior high school students.